Club Licencing Regulations (CLR) on Infrastructure Aspect in PSSI Bandung and Persib Bandung Football Club: An Evaluation Study - Lukman Widjayana; Moch Asmawi; James Tangkudung; Anggi Setia Lengkana (UNIB Press, 2022)
This study aims to evaluate infrastructure aspects hated on the Club Licensing Regulation (CLR) of the City Association (Askot) of the All Indonesian Football Association (PSSI) and the Persib Bandung Football Club (Persib), as well as the effectiveness of in improving the performance of both: Askot and the Persib Bandung. This research is an evaluative study with a Context, Input, Process rind Product (CIPP) review. It has relevance value because of its holistic approach to evaluation to provide a very detailed and broad picture of a program, from its context to the implementation process. Context stages include goals and objectives, legal law and policies, legality, and determination of organizational structure. Input stages include stadium eligibility, control room availability, capacity, first-aid availability, doping control room, field specifications, press and media facilities, audience seats, and supporting accommodation. The process stages include basic rules, operating procedures, facility use, maintenance, and monitoring. The product stages include physical fitness, athlete skills, and club achievement. The process reaches 30.0% in the